Selective carboxylation of reactive benzylic C–H bonds by a hypervalent iodine(III)/inorganic bromide oxidation system - Dohi, Toshifumi; Ueda, Shohei; Iwasaki, Kosuke; Tsunoda, Yusuke; Morimoto, Koji; Kita, Yasuyuki (Beilstein Journal of Organic Chemistry, 2018)
An oxidation system comprising phenyliodine(III) diacetate (PIDA) and iodosobenzene with inorganic bromide, i.e., sodium bromide, in an organic solvent led to the direct introduction of carboxylic acids into benzylic C–H bonds under mild conditions. The unique radical species, generated by the homolytic cleavage of the labile I(III)–Br bond of the in situ-formed bromo-λ3-iodane, initiated benzylic carboxylation with a high degree of selectivity for the secondary benzylic position.
Keywords: carboxylic acids; C–H activation; iodine; oxygenation; radicals